Menakar Konsistensi Asas Audi et Alteram Partem dalam Putusan Verstek perdata Elektronik: Tantangan dan Solusi Hukum Progresif - Nur Faliza Pulumoduyo (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze the consistency of the application of the audi et alteram partem principle in default judgments in electronic civil court proceedings (e-Court) in Indonesia in 2025. A normative legal research method was applied using a legislative and case-based approach, utilizing primary legal materials (PERMA No. 1/2019 jo. PERMA No. 7/2022, HIR/RBg, and final court decisions), secondary materials (legal doctrine, progressive legal theory), and tertiary materials (legal dictionaries, encyclopedias). The research findings revealed three main challenges: the unreliability of electronic notification mechanisms, gaps in digital literacy and technological infrastructure, and inconsistencies in default judgment practices across courts, which create uncertainty in the process and erode public trust. Through the concept of progressive law, normative reforms are proposed, including double verification procedures and clarification periods, the implementation of a hybrid hearing model, the development of an AI-based integrated notification system, technical and digital ethics training for judicial officials, digital legal literacy education for the public, and online legal assistance for vulnerable groups. These recommendations are directed at the Supreme Court, policymakers, and legal practitioners to establish an inclusive, accountable, and humane electronic judicial system, ensuring that the right to be heard and due process of law remain safeguarded.